Enhanced seismic isolation and energy dissipation approach for the aboveground negative-stiffness-based isolated structure with an underground structure. (April 2023) - Zhao, Zhipeng; Wang, Yanchao; Chen, Qingjun; Qiang, Hongfu; Hong, Na
Graphical abstract: Highlights: Novel negative-stiffness amplification system-enabled isolation system (NSAS-IS). NSAS-IS applied to underground structure–soil–aboveground structure (USSAS) system. NSAS-IS with enhanced energy dissipation efficiency and isolating effects for USSAS. Design framework and necessity to consider USSAS interaction into NSAS-IS design. NSAS-IS diminishes the adverse effects acting on the underground structures. Abstract: Aboveground structures are increasingly being built in proximity to underground facilities to produce synthetic functions in an intensive space. Targeting multi-seismic performance upgradation and enhanced vibration decoupling, a negative-stiffness amplification system-enabled isolation system (NSAS-IS) is proposed for an aboveground structure within a coupled underground-structure–soil and aboveground-structure–soil system to develop a novel interaction system. The mechanical layout and constitutive model of the NSAS-IS are elaborated, and structural models are established for NSAS-IS-equipped structures built on a fixed base and flexible soil with and without underground structures. The effectiveness and design principle of the NSAS are initially set for the fixed-base condition as a reference, based on which the soil effects with and without the influence of underground structures are distinguished through comparisons. Given the significant impact of flexible soil and underground structures, a generic design framework is proposed for NSAS-ISs employed in underground-structure–soil and aboveground-structure–soil systems. In addition, the enhanced energy dissipation effect of the NSAS and suppressed seismic responses of the soil, ground, and underground structures are illustrated. The obtained results highlight the necessity of incorporating the effects of the soil–structure interaction and underground structures into the performance evaluation and design of NSAS-ISs. Regardless of the soil type and existence of underground structures, NSAS-IS exhibits enhanced energy dissipation efficiency and isolating effects to suppress the seismic performances of the superstructure and isolation layer simultaneously. However, its efficiency could be weakened by complex interactive behaviors when the soil period is close to the isolation period of the NSAS-IS. The proposed design framework can be adopted as a guideline to guarantee the expected isolation effects of the aboveground structure in cases that consider the soil conditions, and simultaneously, the adverse impacts of the aboveground structure imposed on the underground structure can be effectively reduced by the proposed NSAS.